Апробація комплексу програм 3D регіонального моделювання на прикладі геологічних об’єктів Дніпровсько-Донецької западини - Долинський, І.П. (Геоінформатика, 2014)
Стаття присвячена апробації засобів 2D–3D візуалізації цифрових геологічних моделей в галузі нафтогазової геології. Систему досліджено на геологічних об’єктах головної нафтогазоносної провінції України – Дніпровсько-Донецької западини. У функціональному відношенні розглянуто програмні комплекси, які входять до складу цієї системи. Відповідне програмне забезпечення створено на базі ГІС ArcView 3.n з використанням компіляторів Delphy та Fortran і існує у вигляді підсистеми спеціалізованої геоінформаційної системи моделювання геологічних об’єктів. Статья посвящена апробации средств 2D–3D визуализации цифровых геологических моделей в области нефтегазовой геологии. Испытания системы проводились на геологических объектах главной нефтегазоносной провинции Украины – Днепровско-Донецкой впадины. В функциональном отношении рассмотрены программные комплексы, входящие в состав данной системы. Соответствующее программное обеспечение создано на базе ГИС ArcView 3.n с использованием компиляторов Delphy и Fortran и существует в виде подсистемы специализированной геоинформационной системы моделирования геологических объектов. Purpose. The paper is devoted to the testing of software for building, analyzing and visualizing numerical geological models in oil and gas geology.
Design/methodology/approach. The numerical model of the geological object is considered as a complex of 2D models of its properties and internal and external margins. This complex of models is based on the methods of 2D approximation using different experimental and prior data. The results presented by natural for geologists forms of visualization: maps, sections, etc. The software is created as a special geoinformational system based on ArcView 3.n, using Delphy and Fortran compilators.
Findings. The software testing was carried out on the objects of the Donetsk-Dniper basin, namely the Talalaivsko-Artiuhivska, Leliakivsko-Gnedincivska structure groups and the Sribnenska depression in the stratigraphical interval of the oil and gas content – С₁–P₃. The article also discusses the results of building by means of the geoinformational system regional geological models, and their presentation as vertical and horizontal sections, axonometric projections, and stratigraphical cubes. We present the results of testing space analysis means on the examples of clasterization and classification of deposits and perspective structures of the investigated regional objects by structural and geothermal parameters.
Practical value/implications. The authors have developed a suitable and practical geoinformational system for building and analyzing numerical models of geological objects in oil and gas exploration.